Predictors of female students' intentions toward urban forest conservation for climate change mitigation in Iran - Maleknia, Rahim; Svobodova, Kamila (Scientific reports, 2025)
Urban forests serve as a nature-based solution for mitigating climate change. The active participation of diverse community groups, especially women in the conservation of these resources is essential for effectively addressing climate-related challenges. Female high school students, as a critical demographic within the community, can significantly contribute to the management of urban forests, thereby facilitating the achievement of multiple sustainable development goals including SDG 5, SDG 11, SDG 13, SDG 15, and SDG 17. This study explores the behavioral intentions of female high school students in conserving urban forests for climate change mitigation, addressing a critical research gap in understanding the role of youth, particularly females, in environmental conservation. Employing an extended Theory of Planned Behavior (TPB) model, this research integrates Environmental Awareness (EA) and Social Responsibility (SR) alongside traditional TPB constructs to enhance explanatory power. Data was collected from 370 students through a structured questionnaire and analyzed using structural equation modeling. Results reveal that attitudes, perceived behavioral control, EA, and SR significantly influence students' intentions, while subjective norms show no significant effect. The extended model explains 64.9% of the variance in behavioral intentions, a 21.2% improvement over the initial TPB model. These findings underscore the importance of fostering environmental awareness, cultivating a sense of responsibility, and equipping female students with the skills necessary to contribute to urban forest conservation. The study offers actionable insights for policymakers and educators to design targeted initiatives that empower female youth as agents of change in climate action.
Keywords: Climate change; Attitude; zachování přírodních zdrojů; Forests; Students; průzkumy a dotazníky; Female; Írán; Climate Change; Conservation of Natural Resources; Pro-environmental behavior; Environmental awareness; klimatické změny; ženské pohlaví; lesy; Surveys and Questionnaires; Adolescent; lidé; Urban greenspace; úmysl; Iran; Intention; Social responsibility; studenti; mladiství; Humans